Sustainable Tourism Industry in the Areas Around Historical Sites - Hantosh, Israa; Alkinani, Amer (Al-Adab Journal, 2025)
The tourism industry in historical areas faces many challenges that lead to the deterioration of their physical condition and, thus, a decline in their historical value. These challenges may be due to environmental conditions, the local population, the authorities’ neglect of those sites, and the lack of sustainability in the areas surrounding the historical sites. Urban sustainability and thus an increase in tourism, with the emergence of the concept of sustainable tourism as one of the most prominent. Global tourism patterns at the present time are due to their pure and clean approach to preserving natural sites, balancing heritage, protecting the urban environment, preserving its identity, and marketing tourism in a sustainable manner, which benefits all parties involved in the sustainable tourism process that aims to optimize the investment of natural and urban resources and change from traditional tourism to cultural tourism. Therefore, the research problem focused on multiple challenges facing historical areas as a result of urban expansion and changing land uses surrounding historical areas, which may harm cultural heritage and hinder the promotion of the sustainable tourism industry.The research therefore aims to promote sustainable tourism in its intellectual and practical dimensions and its impact on historical regions in order to advance the reality of these regions and reach the highest possible efficiency in support of sustainable development in them in the long term with regard to their developments and impacts (social, economic, and cultural) on those historical regions.